Perancangan Game Edukasi Pengenalan Bahasa Pemrograman Menggunakan Construct 2 - Iedam Fardian Anshori; Salsabila Ayuni Kaffah; Nahdayanti Supa; Rizal Setiawan (Fakultas Teknik Universitas Hamzanwadi, 2022)
Coding or computer programming for children is now increasingly popular. According to various studies, children who learn coding at a very young age will benefit from learning to critically assess situations, explore different perspectives, build creative solutions, and even develop cognitive abilities. But of course the difficulty of the learning process itself is another level, and again, we need to see the fact that children nowadays are more into video games than learning makes this kind of situation become more complex. Therefore, this research was carried out which aims to design and create an Android-based coding introduction educational game called Funcode. Game development is assisted by the Construct 2 game engine and using the waterfall method from the SDLC or System Development Life Cycle. The game is in the form of a module equipped with a quiz by introducing HTML and CSS programming languages, as well as applying a little Computational Thinking material. Based on the blackbox test results, this mobile game called Funcode is successfully runs without any errors on various types of smartphones that have been tested